2012
DOI: 10.1093/toxsci/kfs222
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activation and Inflammation Reactions Involved in Carbamazepine-Induced Liver Injury

Abstract: Drug-induced liver injury is a major safety concern in drug development and clinical pharmacotherapy; however, advances in the understanding of the mechanisms of drug-induced liver injury are hampered by the lack of animal models. Carbamazepine (CBZ) is a widely used antiepileptic agent. Although the drug is generally well tolerated, only a small number of patients prescribed CBZ develop severe hepatitis. In the present study, we developed a mouse model of CBZ-induced liver injury and elucidated the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 31 publications
2
50
0
3
Order By: Relevance
“…This result is consistent with a previous study that KTZ significantly reduced the metabolism-dependent irreversible binding of radiolabeled CBZ to human liver microsomes (Pirmohamed et al, 1992b). In contrast, our previous study reported that cotreatment with TAO or KTZ exacerbated the CBZ-induced liver injury in mice (Higuchi et al, 2012). This controversial result may be attributed to the species differences in the P450-mediated metabolism of CBZ between the mouse and rat.…”
Section: Hepatotoxicity By Carbamazepine Requires Metabolism In Rats 965supporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with a previous study that KTZ significantly reduced the metabolism-dependent irreversible binding of radiolabeled CBZ to human liver microsomes (Pirmohamed et al, 1992b). In contrast, our previous study reported that cotreatment with TAO or KTZ exacerbated the CBZ-induced liver injury in mice (Higuchi et al, 2012). This controversial result may be attributed to the species differences in the P450-mediated metabolism of CBZ between the mouse and rat.…”
Section: Hepatotoxicity By Carbamazepine Requires Metabolism In Rats 965supporting
confidence: 92%
“…The administration method was determined by reference to our previous mouse study of CBZ-induced liver injury (Higuchi et al, 2012). Rats were orally administered CBZ at a dose of 400 mg/kg once daily for 4 days, then 400, 600, or 800 mg/kg on the 5th day.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that valproic acid prevented an inflammation, and carbamazepine could cause an inflammation and hepatic injury as a result of this. 23,24 We couldn't find any information about possible anti-inflammatory effects of phenobarbital. But, in our study, when patients were classified according to the use of the drug, no differences were found in IL-1β and VEGF levels of GCF among the drug groups.…”
Section: Discussionmentioning
confidence: 99%